Barriers and facilitators to deprescribing in primary care: a systematic review. Issue 3 (August 2020) - Doherty, Alison Jayne; Stephani, Anne- Marie; Hill, Ruaraidh; Boland, Paul; Walker, Lauren; Williams, Nefyn Howard; Reed, Janet; Shaw, Beth; Clegg, Andrew J; Hedgecoe, Lynn
No abstract available